Legal protection of children as witnesses in sexual harassment cases based on law no. 11 of 2012 on the juvenile justice system - Asnawi, Asnawi; Hidayat, Rahmat; Maulana, Ayang Fristia; Jumhana, Enjum (Journal of Law Science, 2024)
Children as witnesses in criminal cases often experience vulnerability and require adequate legal protection given the effects of psychological and social trauma they face during the judicial process. The rights of children as witnesses are often not in accordance with the provisions of Law No. 11/2012 on the Criminal Justice System and existing legal protection practices. There are situations where child witnesses do not receive adequate assistance or guidance. This study aims to determine and analyze legal protection, criminal law provisions against the juvenile justice process against children who are used as child witnesses in sexual harassment cases and to find out the obstacles faced by related institutions in the juvenile criminal justice process. The method used in this research uses a normative method carried out by examining the study of library materials or secondary data. The research conducted has a descriptive nature aimed at providing a description of the social symptoms studied. Sexual abuse cases involving children as witnesses or victims are a serious problem in the criminal justice system. Children who become witnesses often face high challenges and risks during the judicial process, both in terms of psychological and legal protection. The research concluded that the protection of children as witnesses in the settlement of criminal cases is very important considering the fact that witnesses and victims often do not receive adequate protection and face intimidation, so they are reluctant to provide testimony in court.